Effect of voltage harmonics on pulse repetition rate of partial discharges - Trotsenko, Yevgeniy; Brzhezitsky, Volodymyr; Protsenko, Olexandr; Chumack, Vadim; Haran, Yaroslav (Technology audit and production reserves, 2017)
The objects of the research are partial discharge processes simulated under the influence of non-sinusoidal voltage. In the context of studying the effect of voltage harmonics on partial discharges, the total harmonic distortion can only be used for rough estimation. The reason for this is that the total harmonic distortion does not take into account the phase angles of the individual voltage harmonic components. Under non-sinusoidal voltage with the total harmonic distortion of 10 % and above, the intensity of the partial discharges in the insulation increases. However, at lower values of the total harmonic distortion, the harmonics can also affect the characteristics of the partial discharges. To solve this problem, it is necessary to carry out a study, increasing the number of voltage harmonics taken into account. To do this, it is possible to use the known three-capacitive equivalent circuit for a dielectric with gas cavity, making appropriate changes to the voltage source. The model was studied using voltage harmonic of the fundamental frequency together with voltage harmonics from the 2nd to the 30th order included. It was found that for the fixed amplitude the phase angle of the voltage harmonics has a decisive influence on the number of partial discharge pulses. In the presence of voltage harmonics, this number can be the same as under the influence of a pure sinusoidal voltage. It can also be 14.3 % less and 14.3 % or 28.6 % greater. In all cases, the value of total harmonic distortion remains the same. The possibility of using high-voltage reference inductive voltage transformers for voltage distortion measurements was studied experimentally. It was found that this is expedient for the region of the maximum value of the magnetic permeability of their magnetic cores, which corresponds to a range of 80–120 % of the transformer rated voltage. Mobile laboratories for checking high-voltage transformers on-site with the addition of appropriate equipment can simultaneously be used to measure a number of power quality indices.